Simple and analytical function for the Stark profile of the Hα line and its application to plasma characterization. (September 2018) - Díaz-Soriano, A.; Dimitrijević, M.S.; Alcaraz-Pelegrina, J.M.; Sarsa, A.; Yubero, C.
Highlights: This method fits the Stark profiles for the Hα line based on the CS model to an analytical function in order to simplify the calculation of the theoretical profile, which is obtained from the convolution of different functions corresponding to different phenomena: Doppler, Van der Waals, Instrumental effect, among them. This method does not assume Lorentzian shape for the Stark contribution, since it is well known that this consideration is not very accurate. The application of this method can be very useful because it provides three values for plasmas characterization at the same time: the electron density and Gaussian and Lorentzian widths. Abstract: The increasing application of plasma based technologies over a wide range of fields has led to the necessity of an optimal determination of the characteristic parameters of the plasma systems. Optical Emission Spectroscopy techniques have been proved as an excellent tool to that end. These techniques are based on the collection and analysis of the radiation coming from the plasma, being classified between molecular and atomic emission. Among atomic emission lines, Hydrogen Balmer series lines are the most measured. The Hβ line is usually the most employed one for plasma diagnosis but under some conditions, the Hβ line is not always detectable and only the Hα line can be detected. For these lines, it is well known that their shapes are the result of the convolution of three profile types: Lorentzians, Gaussians and Starks. But while the first two types present analytical functions, models explaining the Stark profile do not offer these. So, in this paper we propose an accurate analytical function for the Stark profile of the Hα line allowing improving the determination of characteristic parameters of plasma with respect to the methods traditionally used.